Peningkatan Kapasitas Lansia dalam Membaca dan Menulis Alfabet di Desa Wonosari, Kecamatan Grujugan, Kabupaten Bondowoso - Rida Mahmudah; Chabib Musthofa (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
This community service program aims to enhance the literacy skills of the elderly in Wonosari Village, Grujugan, Bondowoso, by teaching them how to read and write the alphabet. Literacy, particularly reading and writing, is an essential skill for every individual, yet it remains a challenge for many elderly people in rural areas due to limited access to education during their younger years. Through the Asset-Based Community Development (ABCD) approach, which focuses on utilizing the community's existing assets, this program successfully engaged elderly participants in a structured learning process. The elderly were taught to read and write the alphabet over seven sessions, leading to increased self-confidence and independence in their daily lives. The program not only improved their literacy but also fostered greater social inclusion and community participation. This initiative demonstrates that with the right approach and support, the elderly can continue to develop and contribute to their community.